PENGEMBANGAN MEDIA WORDWALL DENGAN METODE SILABA DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 1 SDN GUNUNGPATI 02 KOTA SEMARANG - Tyas Palupi, Anggini; Kurniana Bektiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop Wordwall media with Silaba method in improving Indonesian language learning outcomes of grade 1 students. This study uses the Research and Development (R&D) method. The subjects were 31 grade 1 students from SDN Gunungpati 02 Semarang City. The collection techniques were documentation, observation, and test. The results of this study concluded that the media with the silaba method can improve the learning outcomes of grade 1 students of SDN Gunungpati 02 Semarang City.